Internalisasi Nilai Karakter Religius Peserta Didik di MA Negeri 1 Model Bojonegoro - Bagus Novianto; Haris, Abd.; Huda, Miftahul (Al Hikmah: Jurnal Studi Keislaman, 2023)
Abstract, This article contains a discussion of research on the role of madrasas in cultivating religious character values ​​in students. The object in this article was carried out at the Bojonegoro Model 1 State Madrasah Aliyah (MA). The type of research used in this article is qualitative. By conducting observations, interviews, and documentation. The focus in this article is on (1) the concept of internalizing students' religious character values; (2) Application of the internalization of religious character values ​​of students; (3) Implications of internalizing the religious character values ​​of students in State MA 1 Model Bojonegoro. The results of this study indicate that (1) State Senior High School 1 Model Bojonegoro has a coaching concept. habituation, and exemplary; (2) In applying religious character values, State MA 1 Model Bojonegoro implements it through strengthening formal material; Implementation of religious program activities; Providing exemplary advice; Giving educational punishment as a consequence of the violation committed; (3) The implications for internalizing religious character values ​​are that students show that they can accept the concept and implement efforts to internalize religious character values. This is evidenced in the daily habitual behavior observed by researchers and data from the Counseling Guidance team which shows that within 5 months the level of violations committed by students is very minimal. So it can be concluded that the internalization of religious character values ​​in the Bojonegoro Model 1 State MA has been well internalized. Keywords: Internalization, Religious Character, Students.